2013
DOI: 10.2340/00015555-1368
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids Reduce Formation of Keratin Aggregates in Heat-stressed Immortalized Keratinocytes from an Epidermolytic Ichthyosis Patient with a KRT10 Mutation*

Abstract: Epidermolytic ichthyosis (EI) is an autosomal dominant epidermal skin fragility disorder caused by mutations in keratin 1 and 10 (K1 and K10) genes. Mutated keratins form characteristic aggregates in vivo and in vitro. Some patients benefit from retinoid therapy, although the mechanism is not fully understood. Our aim was to demonstrate whether retinoids affect the formation of keratin aggregates in immortalized EI cells in vitro. EI keratinocytes were seeded on cover slips, pre-treated or not with retinoids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Apart from architectural support, keratins have a crucial role in keratinocyte differentiation, growth, and proliferation (Santos et al, 2002;Paramio et al, 2007). Disruption of these non-structural functions due to mislocalization (Choate et al, 2010) or gain of potentially toxic functions by aggregation (Li and Törmä, 2013) may determine clinical outcomes of specific keratin mutations. Rod domain mutations found in severe EI show accumulation of cytotoxic keratin aggregates in suprabasal keratinocytes, epidermolysis, disrupted epidermal differentiation, and basal cell hyperproliferation (Fuchs et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from architectural support, keratins have a crucial role in keratinocyte differentiation, growth, and proliferation (Santos et al, 2002;Paramio et al, 2007). Disruption of these non-structural functions due to mislocalization (Choate et al, 2010) or gain of potentially toxic functions by aggregation (Li and Törmä, 2013) may determine clinical outcomes of specific keratin mutations. Rod domain mutations found in severe EI show accumulation of cytotoxic keratin aggregates in suprabasal keratinocytes, epidermolysis, disrupted epidermal differentiation, and basal cell hyperproliferation (Fuchs et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Keratin 10 aggregation has been reported in keratinocytes under conditions of cell stress . KRT10 immunostaining appeared normal in both control‐ and single dose‐treated keratinocytes during early differentiation (i.e.…”
Section: Resultsmentioning
confidence: 86%
“…It has also been reported to be of potential benefit in epidermolytic ichthyosis, an uncommon genodermatosis caused by mutations in keratins 1 or 10, when Reichelt et al have shown that increased stability of keratins 5 and 14 could lead to the formation of normal epidermis in K10-null mice [97]. Furthermore, treatment of immortalized cell lines from a KRT10-mutated epidermolytic ichthyosis patient with all-trans retinoic acid led to a 200-fold decrease in mRNA expression of K10, accompanied by decreased keratin aggregation [98].…”
Section: Treatment Of Keratin-related Skin and Hair Genetic Disordersmentioning
confidence: 99%